Serine protease inhibitor from hemolymph of green mussel, perna viridis - Khan, M. S.; Goswami, U.; Rojatkar, S. R.; Khan, Mohammad Islam (Bioorganic & Medicinal Chemistry Letters, 2008)
Bioactivity guided fractions of cell-free hemolymph of bacterially challenged marine mussel, Perna viridis led to the isolation of a novel quaternary alkaloid 1, which was identified by its spectral data. The isolated molecule 1 has been found to be a potent serine protease inhibitor ( SPI) showing IC(50) and K(i) values of 102.5 and 97.1-104.68 mu M, respectively. The E(t)/K(i) value of SPI is 6.3, whereas E(t)/K(m) value is 1.04. The Van't Hoff analysis showed that the value of K(i) decreases with increase in temperature, and the binding of the inhibitor is entropically driven. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: hemolymph; Natural product; Perna viridis; protease inhibitor